RETROSPECTIVE ANALYSIS OF THE DEVELOPMENT OF THE RUSSIAN GOLD MINING INDUSTRY - Suglobov, A.E; Vorontsov, Y.N (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The article discusses the historical aspects of gold mining in Russia over the past two hundred years. It should be noted that a person's interest in gold is due to several reasons. First, according to a certain theory, the origin of the precious metal, namely gold, was in the primordial matter of the formation of the planet Earth. According to the same theory, the distribution of gold was relatively uniform. The formation of gold occurs in the earth's interior at enormous temperatures and Titanic pressure. Natural phenomena such as earthquakes, volcanic eruptions, and mountain formation processes cause gold to rise to an accessible depth for human mining. According to legend, gold is one of the first metals that was discovered by a man, attracting with its beauty and surprising with its properties. Nature has generously endowed our country with mineral resources that are rich in loose deposits available for development. The development of gold mining led to the settlement of the East of the country and the development of this region. The growth of the state and the expansion of trade have determined the relevance of the production of precious "money" metal. In 1745, the first Russian Deposit of native gold was discovered in the Urals. Since 1747, there is a countdown of laying the mines that gave rise to the rich mine "Initial" and a year later, 340 kg of Gold was extracted. The end of the XVIII century. for Russia became famous for the fact that in the upper reaches of the Iset river basin, 140 gold bands were found. The gold-bearing area of deposits in the Iset valley was named "Yekaterinburg Golden valley".